Analysis Of Conventional Methods And Activity Based Costing (ABC) Methods In Determining Product Cost Unit In Bagoster Business Baubau City - Herman; Irmawati Alimuddin; Winda Ayu Virginia; Muarif Leo; Muhammad Akbar (Politeknik Negeri Madiun, 2022)
The selling price of a product can be a company's strength or weakness, so an appropriate cost recording method is needed. This study aims to compare the recording of product costs a unit using the conventional method and the activity based costing (ABC) method in the Bagoster Business in Baubau City using descriptive statistical quantitative methods. The types of products produced are Fried Meatballs, Monster Fried Meatballs, Tofu Walik, and Monster Fried Indomie. Fried Meatballs, the cost a unit of the conventional method and the ABC method were Rp 12,025.71 and Rp 11,955.66, respectively. Monster Fried Meatballs, the cost a unit for the conventional method and the ABC method is Rp 12,250 and Rp 15,543.85, respectively. Tofu Walik, the unit costs of the conventional method and the ABC method are Rp. 13,129 and Rp. 13,965,157, respectively. Monster Fried Indomie, the cost a unit for the conventional method and the ABC method is Rp. 15,025 and Rp. 11,435.816, respectively. Results of the study, two methods present different results, but ABC method provides a more accurate recording because it charges costs based on cost activities that occur in the product, not equating costs to all products like the conventional method pattern